Reflections in an Eastern Mirror, or Performance of a French Vaudeville in Russia - Woodside, Mary (Canadian University Music Review / Revue de musique des universités canadiennes, 2003)
Exceedingly popular in their day, Russian vaudevilles and opera-vaudevilles of the first third of the nineteenth century are not available in modern orchestral scores. Although many of these musical comedies are known to be adapted from French works, for the most part the original French titles are unknown, as are the differences in French and Russian treatments of musical numbers. Focussing primarily on Pisarev's Babushkiny popugai [Grandma's Parrots] (St. Petersburg, 1819), this article compares the original French vaudeville with its Russian adaptation on several points: libretto, performance venues, and musical treatment, the latter based in part on manuscript sources of Alexei N. Verstovsky's orchestral scores.